Phase Equilibria and Crystal Growth in the Alkali Antimonate Systems Sb(2)O(4)–NaSbO(3/) Sb(2)O(4)–KSbO(3/), and Sb(2)O(4)–NaSbO(3)–NaF - Waring, J. L. (J Res Natl Bur Stand A Phys Chem, 1976)
Phase equilibrium diagrams have been constructed from experimental data for the systems Sb(2)O(4)–NaSbO(3), Sb(2)O(4)–KSbO(3), and Sb(2)O(4)–NaSbO(3)–NaF. The system Sb(2)O(4)–NaSbO(3) contains only an intermediate pyrochlore type solid solution with a maximum melting point of 1490 °C at a Na:Sb atom ratio of 3:5. The Sb(2)O(4)–KSbO(3) system contains in addition to the pyrochlore phase a compound 3K(2)O • 5Sb(2)O(5) which melts congruently at about 1450 °C and two polymorphs of K(2)O • 2Sb(2)O(5). The low temperature form of K(2)O • 2Sb(2)O(5) was found to be monoclinic P2(1)/c with a = 7.178, b = 13.378, c = 11.985 A, β = 124°10′. The melting point of Sb(2)O(4) was found to be 1350 ± 5 °C and NaSbO(3) and KSbO(3) both melt congruently at 1555 ± 5 °C and 1410 ± 5 °C respectively. The previously reported cubic form of KSbO(3) was found to be a K(+) deficient phase stabilized by reaction with atmospheric moisture. A similar cubic phase which appears to be a good Na(+) ion conductor can be synthesized in the ternary system NaSbO(3)–Sb(2)O(4)–NaF.